2015
DOI: 10.1111/jace.13982
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties of Rare‐Earth Monosilicates for EBC on Si‐Based Ceramic Composites

Abstract: Rare-earth (RE) monosilicates are promising candidates as environmental barrier coating (EBC) materials for ceramic matrix composites for aerospace applications. Five rare-earth monosilicate materials have been investigated: Y2SiO5, Gd2SiO5, Er2SiO5, Yb2SiO5, and Lu2SiO5 produced from RE oxides and silica starting materials pressed and sintered at 1580°C under flowing air. Relative densities above 94% were obtained for all samples and ceramics were made containing 85–100 wt% of the RE monosilicate according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(56 citation statements)
references
References 46 publications
2
54
0
Order By: Relevance
“…Y, Gd, Yb and Lu monosilicates were sintered for 3 hours at 1580˚C at a heating rate of 10˚C min -1 in a box furnace in air. However, to produce Er 2 SiO 5 , 12h sintering was necessary to obtain dense samples [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Y, Gd, Yb and Lu monosilicates were sintered for 3 hours at 1580˚C at a heating rate of 10˚C min -1 in a box furnace in air. However, to produce Er 2 SiO 5 , 12h sintering was necessary to obtain dense samples [18].…”
Section: Introductionmentioning
confidence: 99%
“…Y, Gd, Yb and Lu monosilicates were sintered for 3 hours at 1580˚C at a heating rate of 10˚C min -1 in a box furnace in air. However, to produce Er 2 SiO 5 , 12h sintering was necessary to obtain dense samples [18].Water vapour corrosion tests were conducted at 1350 ˚C for 50, 100 and 166 h in 90% water:10% air ratio with flow rate of 40 ml/min in an alumina tube (50 mm diameter and 1200 mm length) furnace ((Lenton, Hope, UK) at a heating and cooling rate of 10 ˚C min -1 and 20 ˚C min -1 respectively. Sample dimensions were 10 mm diameter and 3 mm thick.…”
mentioning
confidence: 99%
“…The top ceramic layer (rare earth silicate) is mainly used to block the entry of water vapor, and the mullite layer can reduce the mismatch of coefficients of thermal expansion (CTEs) and alleviate thermal stresses across the layers [7]. Among rare earth silicates, Yb 2 SiO 5 (YbMS) and Yb 2 Si 2 O 7 (YbDS) are the most promising EBC materials since they have several advantages [8]. These include a high melting point, low volatility [9], excellent mechanical properties, low thermal conductivity, and good phase structure stability above 1400 • C [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…There are several key issues in selecting EBC materials, including low oxygen permeability, suitable coefficient of thermal expansion (CTE), excellent phase stability . Recent researches have demonstrated that rare earth silicates are promising candidates of EBC materials due to their superior high‐temperature stability, relatively low CTE, long durability in water vapor and excellent chemical compatibility with silicon‐based ceramics …”
Section: Introductionmentioning
confidence: 99%